Ship losses and the growth of Roman harbour infrastructure - Robinson, DJ; Rice, CM; Schörle, K (Equinox Publishing, 2020)
This study analyses regional trajectories in Mediterranean coastal developments between ca. 200 bc and ad 200, the time of a peak in maritime activities as recorded archaeologically through shipwreck evidence. The aim is to test the proposition that the development of harbour infrastructure should be followed by a decline in shipwrecks around coastal areas. The inference is that, economically speaking, investing in harbours would result in faster and safer trans-shipment areas and enable regions to cope better with intensifying trade, while the high costs of harbour infrastructure would be offset by a reduction in the loss of ships, and hence loss of capital. In reality, however, the relationship between shipwreck data and local harbour infrastructure in the ancient Mediterranean is far more complex. Here we discuss two coastal regions: central Tyrrhenian Italy and southern France. We suggest the realization of a need for the substantial development of infrastructure in order to cope with intensifying trade is a phenomenon that predates the Roman Imperial period.